MRM2 and MRM3 are involved in biogenesis of the large subunit of the mitochondrial ribosome - Rorbach, Joanna (The American Society for Cell Biology, 2014)
Defects of the translation apparatus in human mitochondria are known to cause disease, yet details of how protein synthesis is regulated in this organelle remain to be unveiled. Ribosome production in all organisms studied thus far entails a complex, multistep pathway involving a number of auxiliary factors. This includes several RNA processing and modification steps required for correct rRNA maturation. Little is known about the maturation of human mitochondrial 16S rRNA and its role in biogenesis of the mitoribosome. Here we investigate two methyltransferases, MRM2 (also known as RRMJ2, encoded by FTSJ2) and MRM3 (also known as RMTL1, encoded by RNMTL1), that are responsible for modification of nucleotides of the 16S rRNA A-loop, an essential component of the peptidyl transferase center. Our studies show that inactivation of MRM2 or MRM3 in human cells by RNA interference results in respiratory incompetence as a consequence of diminished mitochondrial translation. Ineffective translation in MRM2- and MRM3-depleted cells results from aberrant assembly of the large subunit of the mitochondrial ribosome (mt-LSU). Our findings show that MRM2 and MRM3 are human mitochondrial methyltransferases involved in the modification of 16S rRNA and are important factors for the biogenesis and function of the large subunit of the mitochondrial ribosome.